Applying fuzziness to enemy behavior in a serious game - Zapirain, Esteban (2017)
This work presents the design and implementation of a real time fuzzy logic Mamdani-type controller for enemy artificial intelligence (AI) in a serious game. The game chosen is Power Down the Zombies, a serious game with educational purposes. A prototype of the game is coded in Javascript, and a comparison is made between the fuzzy enemy behavior and the classical, crisp one. The results of this work show the feasibility of fuzzy logic systems as a highly adequate choice for modelling human-like behaviour and decision making for an element in a videogame, with minimum processing costs.